iPSCs: A Minireview from Bench to Bed, including Organoids and the CRISPR System - Andrés Javier Orqueda; Carla Alejandra Giménez; Federico Pereyra-Bonnet (Stem Cells International)
When Dolly the sheep was born, the first probe into an adult mammalian genome traveling back in time and generating a whole new animal appeared. Ten years later, the reprogramming process became a defined method of producing induced pluripotent stem cells (iPSCs) through the overexpression of four transcription factors. iPSCs are capable of originating virtually all types of cells and tissues, including a whole new animal. The reprogramming strategies based on patient-derived cells should make the development of clinical applications of cell based therapy much more straightforward. Here, we analyze the current state, opportunities, and challenges of iPSCs from bench to bed, including organoids and the CRISPR system.